2010
DOI: 10.1007/s11274-010-0364-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and plant-growth related features of Burkholderia spp. from sugarcane roots

Abstract: Brazil is the largest sugarcane producer in the world, mainly due to the development of different management strategies. Recently, microbial-plant related studies revealed that bacterial isolates belonging to the genus Burkholderia are mainly associated with this plant and are responsible for a range of physiological activity. In this study, we properly evaluate the physiological activity and genetic diversity of endophytic and rhizospheric Burkholderia spp. isolates from sugarcane roots grown in the field in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 42 publications
3
40
0
10
Order By: Relevance
“…Genus Burkholderia sp. was identified in rice (Baldani et al, 2000;Oliveira et al, 2002), maize (Riggs et al, 2001) and sugarcane Luvizotto et al, 2010;Beneduzi et al, 2013). In South of Brazil, Beneduzi et al (2013) identified two species: Burkholderia phenazinium and Burkholderia cepacia, but in our study we found a different species (B. cenocepacia).…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Genus Burkholderia sp. was identified in rice (Baldani et al, 2000;Oliveira et al, 2002), maize (Riggs et al, 2001) and sugarcane Luvizotto et al, 2010;Beneduzi et al, 2013). In South of Brazil, Beneduzi et al (2013) identified two species: Burkholderia phenazinium and Burkholderia cepacia, but in our study we found a different species (B. cenocepacia).…”
Section: Discussionmentioning
confidence: 40%
“…(Oliveira et al, 2002) and Burkholderia sp. Luvizotto et al, 2010). Some species were also found and described, such as: Bacillus polimixa (Rennie et al, 1982), Pantoea agglomerans (Loiret et al, 2004) and Gluconacetobacter diazotrophicus (Perin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence is 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 characteristic of nitrogen-fixing bacteria (Marin et al, 2003;Ando et al, 2005;Luvizotto et al, 2010;Shu et al, 2012). Also, our results indicate that Poly PCR primers (Poly et al, 2001) were able to amplify nifH sequences of pineapple endophytes DNA; however, the amplification efficiency differed between them (Figure 2).…”
Section: Discussionmentioning
confidence: 71%
“…These genera have been isolated from different plant hosts, indicating a wide host range. Enterobacteria have been isolates from citrus, cocoa, eucalyptus, soya bean, and sugarcane 27 , whereas Burkholderia are associated in roots of sugarcane 28,29 , rice 30 , and maize 29 . In bamboo, previous research found one species of Enterobacter and six species of Burkholderia from a total number of 56 species of bacteria from root tissue, rhizosphere, and rhizoplane 3 , and B. pyrrocinia is common to this study.…”
Section: Selection Of Phosphate-solubilizing Bacteriamentioning
confidence: 99%